MANAGEMENT AND ASSESSMENT OF INDETERMINATE (U3) THYROID NODULES: A 5-YEAR MULTISITE RETROSPECTIVE STUDY - Patel, Ravi; Conybeare , Alison; Panesar , Harrypal; Badrol, Sara; Sood, Salil (Journal of Ayub Medical College Abbottabad, 2023)
B Background: The U grading of Ultrasound scan (USS) is used to assess the likelihood of malignancy in a thyroid nodule and help determine those that warrant an FNAC confirmation. All those of a U3-5 warrant an FNAC for confirmation and typing. This study aims to review the follow-up practice and the likelihood for picking up a malignancy on subsequent USS and FNAC, for those determined as an indeterminate U3 nodule. Methods: We retrospective reviewed the trust database (Portal) for patients who had a U3 nodule reported on USS identified, and clinical, operative and outcomes data were analysed. Results: 258 scans were identified over a 5-year period. The average age was 59 (range 15-95) years old at first USS with a female to the male sex ratio of 4:1. The average number of USS that each patient prior to final diagnosis had averaged at 2.8 (range 1-12). Of those with an initial Thy status, 64 (33%) were benign (Thy2) and a further 49 (25%) were non-diagnostics (Thy1). Over time, only 7 nodules were upgraded to a potential malignancy. Of those who underwent surgery, a final histological diagnosis was obtained in 41 cases. Only Thy1, 2 and 3f produced benign final histology results. Conclusion: For those indeterminate (U3) nodules of Th1-3f, electing for a watch and wait management strategy is reasonable for up to 2.5 years and 4 follow-up scans at an interval of 6-12 months should be implemented. A Thy2 result on a U3 nodule should not be taken as completely reassuring, a high index of suspicion of malignancy must be maintained.